Attitudes toward Women's Education in Afghanistan: Empirical Evidence from a Nationwide Survey - Mohammad Haroon Asadi; Mohammad Reza Farzanegan (CESifo GmbH, 2024)
This study investigates men's attitudes toward women's education in Afghanistan, focusing on primary, secondary, and tertiary levels, as well as studying in another province or abroad, through the lens of identity theory and the intra-household bargaining framework. We use data from Afghan surveys conducted by the Asia Foundation from 2014 to 2021 across 34 provinces and apply multivariate regression analysis with a comprehensive set of covariates. Our findings reveal that men's attitudes toward women's education are predominantly negative, notably in rural areas. However, women's contributions to household income significantly mitigate these negative attitudes, particularly toward secondary education, followed by tertiary education, and studying in other provinces or abroad. Moreover, fear of insecurity in society amplifies the negative attitudes of men toward women's education. This research underscores the potential of increased financial contributions by women to transform gender attitudes and promote educational equality in Afghanistan.
Keywords: C83; D63; I24; I25; J16; 330; education; gender gap; attitudes; education inequality; security; Afghanistan; survey